Evaluating the forensic informativeness of mtDNA haplogroup H sub-typing on a Eurasian scale - Pereira, L (2006)
The impact of phylogeographic information on mtDNA forensics has been limited to the quality control of published sequences and databases. In this work we use the information already available on Eurasian mtDNA phylogeography to guide the choice of coding-region SNPs for haplogroup H. This sub-typing is particularly important in forensics since, even when sequencing both HVRI and HVRII, the discriminating power is low in some Eurasian populations. We show that a small set (eight) of coding-region SNPs resolves a substantial proportion of the identical haplotypes, as defined by control-region variation alone. Moreover, this SNP set, while substantially increasing the discriminating efficiency in most Eurasian populations by roughly equal amounts, discloses population-specific profiles.